Clinical Observation of Patients with Post-stroke Fatigue in Community Treated with Buyang Huanwu Decoction - Caide YE; Wugeng XUE; Hao WU; Jinxiu DUAN; Xiumei LIU; Min KONG; Zhigang CHEN (康复学报)
Objective:This study was aimed to observe the clinical effect of modified Buyang Huanwu decoction in treating patients from community with post-stroke fatigue.Methods:Forty-four eligible patients from community with post-stroke fatigue were randomly assigned to the control group (24 cases) and the treatment group (20 cases). Patients in the control group were administered with routine treatment, while patients in the treatment group were given modified Buyang Huanwu decoction according to their signs and symptoms. After 4 weeks, the severity of fatigue (FSS) and quality of life were assessed.Results:Compared to pre-treatment, both twogroups showed significant improvement in fatigue severity and quality of life (P<0.05, P<0.01); the treatment group demonstrated significant better effect on FSS compared to the control group (P<0.01).Conclusion:The modified Buyang Huanwu decoction can significantly ameliorate fatigue, improve quality of life in patients with post-stroke fatigue and reveal good clinical efficacy.